Preparation of antimicrobial polyamide fibers based on surface treatment - Li, Lei; Zhu, Donghong; Kong, Fanmin; Xiao, Ang; Zhang, Ziling; Wang, Haoqi; Yao, Weizhou; Duan, Yutian (Nano and Medical Materials, 2025)
Antibacterial nylon fiber, a crucial functional material, has demonstrated substantial potential for applications in medical, textile, food packaging, and other fields. While conventional nylon fibers possess excellent mechanical properties, their lack of inherent antimicrobial functionality has spurred research into surface treatment methods, including modification and post-finishing techniques. These approaches enable the integration of antibacterial agents such as silver ions, copper ions, and chitosan while preserving fiber integrity. Despite this progress, challenges persist in durability, biocompatibility, and economic feasibility, driving ongoing innovation. This review focuses on surface treatment methods, including chemical modification, dyeing, and post-finishing, covering antibacterial agents, and antimicrobial performance, providing insights into structure-property relationships and optimization strategies. The advancement of antibacterial nylon fibers not only meets critical healthcare demands but also aligns with global sustainability goals, offering innovative solutions with significant societal and economic impact.